STRATEGI KEPALA MADRASAH DALAM MENGATASI RESISTENSI PERUBAHAN KURIKULUM MERDEKA DI MADRASAH ALIYAH MUTIARA AULIA SEI MENCIRIM SUNGGAL - Intan Nur’aini; Syukri, Makmur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the strategies employed by the principal of a madrasah in addressing resistance to change during the implementation of the Merdeka Curriculum at Madrasah Aliyah Mutiara Aulia Sei Mencirim Sunggal. This study employs a qualitative approach using descriptive methods, with data collected through observation, interviews, and documentation. The results of the study indicate that teacher resistance manifests in various forms, such as a lack of understanding of the Merdeka Curriculum concept, difficulties in adapting project-based learning methods, limited use of technology, and a mindset that remains conventional. The madrasah principal’s strategies for addressing resistance are carried out through managerial functions. During the planning stage, the principal conducts outreach and develops work programs in a participatory manner. In the organizing stage, tasks were assigned and a curriculum team was formed. This was followed by the implementation stage, where the principal applied a transformational leadership approach, providing training, mentoring, and motivation to teachers. Meanwhile, during the monitoring stage, periodic evaluations were conducted to ensure the successful implementation of the curriculum. The research results also indicate that these strategies were effective in increasing teachers’ acceptance of the changes, although several challenges remain that require ongoing resolution.